Innovation in environmental technologies in China: the case of Feida’s power plant pollution control equipment - Hofman, Peter S.; Weng, Chenchen; Zhou, Steven Shijin; Zhou, Abby Jingzi (Palgrave Macmillan, 2019)
Innovation is important for developing a strong brand. This chapter introduces a leading provider of environmental solutions for power plants in China. Feida is a company located in the Zhejiang province in China that develops products and technology to remove small particles from the exhausts of coal-fired power plants. The chapter describes the company’s evolution towards a leading company in environmental technology in China and analyzes the role of R&D and innovation in its brand development. The chapter further assesses how the nature of the company’s innovation is connected to the production and functional/user side of the innovation system and institutional environment in which it operates. Feida’s strategy is to expand internationally to foreign markets but it is facing significant challenges in that process.